Association between EAT-Lancet Diet Index and Hypertension Prevalence: The Filipino Women's Diet and Health Study (FiLWHEL). (14th June 2022) - Lee, Heejin; Provido, Sherlyn; Chung, Grace; Hong, Sangmo; Yu, Sung Hoon; Lee, Chang Beom; Lee, Jung Eun
Abstract: Objectives: We examined the association between adherence to EAT-Lancet diet, a diet with human health and environmental sustainability, and the prevalence of hypertension among Filipino immigrant women in Korea. Methods: We included a total of 484 Filipino women aged 34–57 in the Filipino Women's Diet and Health Study (FiLWHEL). Participants' dietary intakes were assessed using the 24-hour recalls in 2014–2016. The EAT-Lancet diet index scores were calculated using the methods used in the European Prospective Investigation into Cancer and Nutrition (EPIC)-Oxford study (EAT-Lancet EPIC) and Malmö Diet and Cancer Cohort Study (EAT-Lancet Malmö). Blood pressures were measured twice by a sphygmomanometer, and two readings were averaged. Hypertension was defined as systolic blood pressure (SBP) ≥140 mmHg or diastolic blood pressure (DBP) ≥90 mmHg or by taking antihypertensive medication. We calculated odds ratio (OR)s and 95% confidence interval (CI)s using the multivariate logistic regression models. Results: A total of 86 hypertensive women were identified. For the EAT-Lancet EPIC index, compared with the 1st tertile, ORs (95% CIs) for hypertension were 1.03(0.52–2.06) for the 2nd tertile and 0.61 (0.30–1.22) for the 3rd tertile (p-trend = 0.17). For the EAT-Lancet Malmö index, compared with the 1st tertile, ORs (95% CIs) for hypertension were 0.44 (0.21–0.89) for the 2nd tertile and 0.77(0.37–1.60) for the 3rd tertile (p for trend = 0.55). Conclusions: Adherence to the EAT-Lancet diet may be associated with a lower prevalence of hypertension among immigrant Filipino women in Korea. Further prospective and intervention studies are warranted to determine the role of a sustainable EAT-Lancet diet in hypertension prevention. Funding Sources: This study was made possible with the support of our funding agencies: Hanmi Pharmaceutical Co., Ltd., Chong Kun Dang Pharm., Handok Inc., and Yuhan Corporation, Seoul, Korea.